Iodido{4-phenyl-1-[1-(1,3-thiazol-2-yl-κN)ethylidene]thiosemicarbazidato-κ2N′,S}{4-phenyl-1-[1-(1,3-thiazol-2-yl)ethylidene]thiosemicarbazide-κS}mercury(II) - Samuel S. R. Dasary; Sri Ranjini Arumugam; Hongtao Yu; Ramaiyer Venkatraman; Frank R. Fronczek (Acta Crystallographica Section E, 2011)
In the title compound, [Hg(C12H11N4S2)I(C12H12N4S2)], the Hg atom is in a distorted square-pyramidal coordination, defined by the iodide ligand, by the S atom of the neutral ligand in the apical position, and by the N atom of the thiazole ring, the thioureido N and the S atom of the deprotonated ligand. The deprotonated ligand intramolecularly hydrogen bonds to the thiazole ring N atom, while the deprotonated ligand forms an intermolecular hydrogen bond to the thiolate S atom. The deprotonation of the tridentate ligand and its coordination to Hg via the S atom strikingly affects the C—S bond lengths. In the free ligand, the C—S bond distance is 1.685 (7) Å, whereas it is 1.749 (7) Å in the deprotonated ligand. Similarly, the Hg—S bond distance is slightly longer to the neutral ligand [2.6682 (18) Å] than to the deprotonated ligand [2.5202 (19) Å]. The Hg—I distance is 2.7505 (8) Å.